Implication of the zinc-epigenetic axis in epidermal homeostasis. Issue 3 (June 2020) - Lee, Mi-Gi; Chae, Sehyun; Nakajima, Kimiko; Ibi, Miho; Sano, Hozumi; Hara, Takafumi; Jo, Hantae; Takagishi, Teruhisa; Cha, Byungsun; Baek, Jin-myoung; Yoshigai, Emi; Ohashi, Takuto; et al.
Highlights: Zinc deficiency induces epidermal malformation with dysregulation of acetylation process in epidermis. Implication of the zinc-epigenetic axis in epidermal homeostasis Possible involvement of zinc transporter ZIP10 in epidermal acetylation